The impact of Hyperoxic training on the development of various physiological variables in basketball players under the age of 18 (Journal of Humanities and Social Sciences Research, 2023)
Basketball is one of the competitive sports activities characterized by variable motor performance, and because of the large number of moves and the proximity of the opponent, as well as the participation of all team players in the offensive and defensive processes, which requires internal physiological adaptations that enable players to acquire special physical abilities and master skills well. The aim of the research is to prepare exercises using hyperoxic and to identify the effect of hyperoxic exercises in developing some physiological variables for players under the age of 18 in basketball. The researcher utilized the experimental technique since it was appropriate for the nature and aims of the research, and the research community was comprised of (12) players from Al-Hilla Basketball Club (2022-2023). To complete the investigation, the researcher has several current methodologies and instruments. The study comprised completing post-tests and statistically processing the data using proper statistical tests and methodologies for a period of (6) weeks, at a pace of (3) training units each week, at a rate of (18) training units. The essential finding is that hyperoxic workouts are extremely crucial in the development of physiological variables. Hyperoxic activities aid in the development of strength and quickness. The most important recommendations are the use of exercises to increase oxygen by trainers and in all sports to save effort and time while achieving training goals; and the use of exercises to increase oxygen during semi-competitions and competitions because of the impact on the development of physiological variables.